BOTTLENECK ANALYSIS AND STRATEGIC PLANNING ON CHILDHOOD DIARRHEA MANAGEMENT IN 6 HIGH PRIORITY DISTRICTS OF GUJARAT - Mihir, Rupani (Indian Journal of Community Health, 2015)
Introduction:Bottleneck Analysis and Strategic Planning exercise was carried out in 6 High Priority Districts (HPDs), under Call-to-Action for RMNCH+A strategy. Rationale: In spite of continued efforts, India is still lagging behind in its MDG goals. Objectives: To identify gaps in childhood diarrhea management and propose strategic options for the same. Materials and Methods: Bottleneck analysis exercisewas carried out based on the Tanahashi model, desk review and focused group discussions between district officials, front-line workers and UNICEF officials. These bottlenecks were pertaining to the availability, accessibility, utilization of services and quality of services being provided by the health department. Elaborating the Tanahashi model for the 6 HPDs, 94% of the front-line workers (FLWs) had stock of Zinc-ORS; 88% FLWs were trained in diarrhea management; 98% villages had at least one FLW trained in diarrhea management; health care seeking for diarrhea cases was 17%; 5.1% diarrhea cases received Zinc-ORS from health worker and 2.4% care takers prepared Zinc-ORS in safe drinking water. Results: The major bottlenecks identified for Childhood Diarrhea management in the 6 High Priority Districts were poor demand generation, unsafe drinking water, poor access to improved sanitation facility and lack of equitable distribution of Zinc-ORS till the front-line worker level. The main strategic options that were suggested for relieving these bottlenecks were Zinc-ORS roll out in scale-up districts, develop IEC/BCC plan for childhood diarrhea management at state/district level, use of Drug Logistics Information Management System (DLIMS) software for supply chain management of Zinc-ORS, strengthening of chlorination activity at household level, monitoring implementation of Nirmal Bharat Abhiyaan (NBA) for constructing improved sanitation facilities at household level and to develop an IEC/BCC plan for hygiene promotion and usage of sanitary latrines. Conclusion: Use of Zinc tablets need to be intensified through an effective scale-up. Adequate demand generation activity is needed.